Modeling the molecular fingerprint of protein-lipid interactions of MLKL on complex bilayers - Ramirez, Ricardo X.; Campbell, Oluwatoyin; Pradhan, Apoorva J.; Atilla-Gokcumen, G. Ekin; Monje-Galvan, Viviana (Frontiers in Chemistry, 2023)
Lipids, the structural part of membranes, play important roles in biological functions. However, our understanding of their implication in key cellular processes such as cell division and protein-lipid interaction is just emerging. This is the case for molecular interactions in mechanisms of cell death, where the role of lipids for protein localization and subsequent membrane permeabilization is key. For example, during the last stage of necroptosis, the mixed lineage kinase domain-like (MLKL) protein translocates and, eventually, permeabilizes the plasma membrane (PM). This process results in the leakage of cellular content, inducing an inflammatory response in the microenvironment that is conducive to oncogenesis and metastasis, among other pathologies that exhibit inflammatory activity. This work presents insights from long all-atom molecular dynamics (MD) simulations of complex membrane models for the PM of mammalian cells with an MLKL protein monomer. Our results show that the binding of the protein is initially driven by the electrostatic interactions of positively charged residues. The protein bound conformation modulates lipid recruitment to the binding site, which changes the local lipid environment recruiting PIP lipids and cholesterol, generating a unique fingerprint. These results increase our knowledge of protein-lipid interactions at the membrane interface in the context of molecular mechanisms of the necroptotic pathway, currently under investigation as potential treatment target in cancer and inflamatory diseases.